Ibero-American Systems for the Dissemination of Scholarly Journals: A Contribution to Public Knowledge Worldwide - Córdoba, Saray (2010)
A vast number of scholarly journals are edited in Ibero-America, together providing a rich picture of the scientific production in this region. However, these journals have traditionally not been part of the international scientific mainstream. Different solutions have been sought to increase their access and visibility, using existing information systems and creating new ones tailored to the region’s needs as well as developing new electronic journals. An analysis of a sample of Latin American electronic journals highlights some features aimed at increasing their visibility. This article also presents the main features of 30 scientific Ibero-American online libraries and discusses their influence on editorial practices throughout the region. Some conclusions are drawn on the challenges and opportunities faced by journals as they seek to strengthen their presence on the international scene.